Clinical features and outcome of pediatric acute lymphoblastic leukemia with low peripheral blood blast cell count at diagnosis. Issue 4 (29th January 2021) - Dai, Qingkai; Zhang, Ge; Yang, Hui; Wang, Yuefang; Ye, Lei; Peng, Luyun; Shi, Rui; Guo, Siqi; He, Jiajing; Jiang, Yongmei
Abstract : Abstract: Peripheral blood (PB) blast cell count on day 8 of prednisone therapy has been considered one of the strongest predictors of outcome in children with acute lymphoblastic leukemia (ALL). However, little is known about the clinical features and prognostic impact of PB blast cell count at diagnosis in these patients. The aim of this study was to evaluate the relationship between initial PB blast cell count and clinical prognosis of pediatric ALL. The study comprised 367 patients with ALL, aged 0 to 14 years, enrolled and treated using the Chinese Children's Leukemia Group-ALL 2008 protocol between 2011 and 2015. The majority (91.6%) of patients were B-cell precursor ALL (BCP ALL), and 8.4% were T-cell ALL (T-ALL). Patients with BCP ALL in the low PB blast cell count group (<1 × 10 9 /L) had significantly superior survival rates to those in the high count group (≥30 × 10 9 /L). In T-ALL, the low count group showed significantly inferior survival rates compared to both the intermediate count group (1–29.9 × 10 9 /L) and high count group. Multivariate analysis revealed that the initial white blood cell count and minimal residual disease at the end of induction therapy were independently predictive of BCP ALL outcome, while risk stratification was shown to be an independent prognostic factor for T-ALL outcome. These results indicated that low blast cell count in PB at diagnosis was associated with different clinical outcomes in patients with BCP ALL and T-ALL, although it was not an independent outcome predictor by multivariate analysis.